(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Type 2 diabetes is considered as a major health burden due to its rising prevalence and disabling, life threatening complications. Dyslipidemia, often coexisting with T2DM as a feature of insulin resistance, is hypothesized to be linked with altered magnesium homeostasis. This study was designed to evaluate the serum magnesium levels and its influence on serum lipids in type 2 diabetics. Lipid profile, serum magnesium (Mg) and fasting serum glucose (FSG) were measured in 30 newly diagnosed normotensive type 2 diabetic patients chosen as cases (Group II) just before introducing any treatment, and was compared with that of 30 healthy controls (Group I). The serum magnesium was found to be significantly lower (p<0.001) and LDL-c was found to be significantly higher (p<0.01) in cases. The correlation analysis revealed a significant negative association of FSG to serum magnesium (r= -0.720), total cholesterol (r=-0.483) and a positive correlation to HDL-c (r=-0.440). However, serum magnesium showed a significant positive relation only with serum HDL-c (r =0.372, p<0.05). Serum magnesium and lipid fractions showed wide range of variation within the normal reference ranges in the newly diagnosed T2D subjects. Further large scale studies are needed to elucidate the association of serum magnesium with lipid profile changes. Estimation of serum magnesium level may prove useful in T2DM with normal or abnormal lipid levels or in those who are prone to develop dyslipidemia or certain complications associated with dyslipidemia. DOI: http://dx.doi.org/10.3329/bjmb.v7i1.18572 Bangladesh J Med Biochem 2014; 7(1): 4-8